The sustainable business model in value creation: process and outcome from business network relationships - Mohd Hadri Mohd Rifin,; Novel Lyndon, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Business network relationships is a business strategy that is an embedded social process through interaction in business activities. Business network relationships help produce the network values that ensure the viability and competitiveness of small and medium enterprises (SMEs). The objective of this study aims to identify the network values from business network relationships in helping the viability and competitiveness of small and medium enterprises (SMEs) owned by Malays (native) through network values exchange activities with the network of actors that make up a network model of business sustainability.This study employed the phenomenological approach through qualitative data collection technique. A total of 20 informants were selected for the study using snowball sampling technique. In-depth interviews were conducted with the informants. Data were transcribed and subsequently analyzed thematically using the ATLAS.ti software. The research found that business network relationships produce the tangible values and intangible values to Malay entrepreneurs. Value exchange activities between social network actors involve information sharing, mentoring, assistance, business support services, advice and business problem solving. The impact of the exchange of social networking values yields various benefits to entrepreneurs ranging from the process of producing quality products and services, marketing strategies, meeting customer needs, business continuity and being able to compete in an increasingly challenging market. The implication of this research is that building a relationship with the actor of social network is a business strategy and a tool for Malay entrepreneurs to benefit in business through the various role of each actor network, resulting in the various network values which complement each other and mutually necessary in building a sustainable business with the aim of economic, social and environmental values. The research showed that Malay entrepreneurs need to build a social network in the micro and macro levels, including social institutions. This study contributes to the social enterprise literature by demonstrating that business network relationshipshelp ensure the viability and competitiveness of SMEsthrough the impact of network values and achieving sustainability goals.